Copper oxide nanoparticles induce collagen deposition via TGF-β1/Smad3 signaling in human airway epithelial cells. Issue 3 (16th March 2018) - Ko, Je-Won; Shin, Na-Rae; Park, Ji-Won; Park, Sung-Hyeuk; Lee, In-Chul; Kim, Joong-Sun; Kim, Jong-Choon; Ahn, Kyung-Seop; Shin, In-Sik
Abstract: Use and application of nanoparticles has increased in recent years. Copper oxide nanoparticles (CuONPs) are one of the most common types of nanoparticles, and they are mainly used as catalysts and preservatives. However, limited toxicity data are available on the toxicity of CuONPs to the respiratory system. We investigated fibrotic responses induced by CuONPs in the respiratory tract and elucidated its underlying mechanism of action in vivo and in vitro experiments. In the mouse model, CuONPs exposure markedly increased transforming growth factor-β1 (TGF-β1) and collagen I expression and Smad3 phosphorylation, combined with elevation of inflammatory mediators including interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α). These alterations were also observed in histological analysis of lung tissue. CuONPs markedly increased inflammatory responses and collagen deposition, accompanied by the elevation of TGF-β1 and collagen I expression in lung tissue. In addition, CuONPs-treated H292 cells showed significantly increased mRNA and protein production of TGF-β1, collagen I, IL-6, and TNF-α; this response was markedly decreased by treatment of a TGF-β1 inhibitor (SB-431542). Taken together, CuONPs induced fibrotic responses in the respiratory tract, closely related to TGF-β1/Smad3 signaling. Therefore, our results raise the necessity of further investigation for the present state of its risk by providing useful information of the toxicity of CuONPs.